At the Crossroads of Gender, Power and Audiovisual Culture: Female Politicians and Businesswomen as Represented in Polish Cinema after 1989 - Chudzicka-Dudzik, Patrycja (Historia i Polityka, 2022)
Contemporary discourse on gender equality in the mass media focuses primarily on analysing news programmes, TV series and advertisements. However, films also constitute powerful cultural stimuli, capable of modifying the attitudes and behaviour of both audiences and the society as a whole. The strength and longevity of their impact lie in their deep roots in the culture in which they operate. For cinematic representations of women and men, this process implies the need to constantly refer to a certain stock of conventions, cultural stereotypes and ways of thinking about gender present in the mentality and social structures of a given community. The same applies to images of women in power in film, which on the one hand are determined by cultural patterns attributed to each gender, while on the other they themselves contribute to their perpetuation in the social consciousness, at the same time creating social images of relations between gender and power in political and economic life. The article discusses this phenomenon in relation to selected Polish films after 1989. The paper will analyse how the roles and behavioural patterns attributed to women were (re)defined in the (changing) public sphere and what the position of characters representing these characteristics was in the narrative of the films.